PENGEMBANGAN MEDIA KARTU MEMORI CERDIK UNTUK PESERTA POSBINDU RW 02 KELURAHAN CIBABAT - Iryanti; Syifa Az-Zahra (Jurnal Kesehatan Siliwangi, 2024)
Background: Diabetes mellitus is a significant health issue affecting many people in Indonesia. West Java is the province contributing to diabetes mellitus with a population of 550.611 million. One of the reasons for the high number of cases is the lack of public knowledge about diabetes prevention using the CERDIK method). Therefore, there is a need for health promotion media regarding CERDIK behavior. Previous research has proven that paired card media is effective in increasing knowledge and changing the attitudes of the target audience (Agustiawan, 2021). Objective: To develop the CERDIK Memory Card Media for Posbindu RW 02 Kelurahan Cibabat participants. Methods: This research uses R&D (Research and Development) with the 4D development model (define, design, develop, disseminate), with a total sample of 32 respondents. Qualitative and quantitative descriptive data analysis. Results: The material feasibility test by material experts showed a result of 86%, categorized as very feasible; the media feasibility test by media experts showed a result of 98%, categorized as very feasible; and the feasibility test results from material and media showed 97% of the targets rated it as very feasible and 3% rated it as feasible. Conclusion: The CERDIK memory card media is very feasible to be used as educational media. Recommendations: Further research on the impact of CERDIK memory card media on other variables or further development of CERDIK memory cards is recommended.